Penerapan Arsitektur Metafora dalam Perancangan Gedung Olahraga Bola Basket di Deli Sport City Sumatera Utara - Syahri, Alvin; Suprayitno, Suprayitno; Nasution, Aulia Muflih (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
This article aims to design a basketball sports hall in Deli Sport City North Sumatra that meets international standards by applying the theme of metaphor architecture. The design is focused on architectural aspects, including the arrangement of sports arenas and supporting facilities. This approach involves searching for ideas through various sources of information about the architectural data of basketball sports buildings and applying metaphorical themes as a solution in designing design ideas that are realized in the form of drawings. Metaphor architecture in the design of basketball sports buildings uses concepts or elements that refer to something familiar or symbolic to create visual and emotional appeal for visitors, and the approach applied is a shape or design element that resembles a basketball or part of a basketball game, such as the line pattern on a basketball, the shape of a net, It gives a dynamic impression and directly connects the building with its function.